Anthropometric typology of male and female rowers using K-means clustering - Forjasz, J. (Journal of Human Kinetics, 2011)
The aim of this paper is to present the morphological features of rowers. The objective is to establish the type of body build best suited to the present requirements of this sports discipline through the determination of the most important morphological features in rowing with regard to the type of racing boat. The subjects of this study included competitors who practise rowing and were members of the Junior National Team. The considered variables included a group of 32 anthropometric measurements of body composition determined using the BIA method among male and female athletes, while also including rowing boat categories. In order to determine the analysed structures of male and female rowers, an observation analysis was taken into consideration and performed by the k-means clustering method.In the group of male and female rowers using long paddles, higher mean values or the analysed features were observed, with the exception of fat-ree mass, and water content in both genders, and trunk length and horizontal reach in women who achieved higher means in the short-paddle group. On the men's team, both groups differed significantly in body mass, longitudinal features, horizontal reach, hand width and body circumferences, while on the women's, they diffred in body mass, width and length of the chest, body circumferences and fat content. The method of grouping used in this paper confirmed morphological differences in the competitors with regard to the type of racing boat.